Cyberlaw in the Perspective of the Effect of Technological Development on Hate Speech on Social Media - I Nyoman Alit Arsana Alit; Ni Wayan Purnawati; I Made Pustikayasa (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
Social media has become an important part of people's lives in the midst of the development of information technology. The development of information technology, especially social media, has many positive impacts and also has negative impacts. The negative impact is hate speech. Technological advances have influenced the perpetrators in committing hate speech because of the availability of facilities and facilities that are easily available. Such facilities include the ease of obtaining a smartphone, the existence of multiple facilities or features, profile cloning. This convenience should be followed by legal awareness, especially the Electronic Information and Transaction Law (ITE Law).